Data Protection Laws Trends: Practice and Debate (Global Journal of Human-Social Science, 2021)
Technological advancement changed the way everything is being done, providing extraordinary benefits and low costs. People and governments are increasingly adopting new technologies to achieve better performance and financial savings. However, those benefits do not come at no cost; technological advancements (such as Cloud Computing, Artificial Intelligence, Robotics, Internet of Things,..etc) involve several security challenges that may expose countries' national securities. The touchstone in this is data. Data has always been central to national security throughout different historical periods. Intelligence agencies' core of work has always been data; however, the mechanisms of getting and securing data evolved throughout history. Nowadays, the applications of different technologies generate enormous amounts of data that are stored in data centers located in different countries. Data could be traveling across countries and between data centers in a routine process so as to balance loads between data centers of the company. This process contains several security risks because countries lose control and sovereignty over the data generated or collected inside their territories, which exposes the core of nation's sovereignty and national security.
Keywords: data protection; data localization; general data protection regulation